2021
DOI: 10.1002/fsn3.2468
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal transit tolerance, cell surface hydrophobicity, and functional attributes of Lactobacillus Acidophilus strains isolated from Indigenous Dahi

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Further cell surface properties of bacterial strains were determined through hydrophobicity. The hydrophobicity of bacterial strains indicated that they could interact with the intestinal mucosa and epithelial cells, thereby ensuring colonization [ 51 ]. Hence, the bacterial strains were incubated with an organic solvent (xylene), and their ability to adhere to the cell surface was tested ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Further cell surface properties of bacterial strains were determined through hydrophobicity. The hydrophobicity of bacterial strains indicated that they could interact with the intestinal mucosa and epithelial cells, thereby ensuring colonization [ 51 ]. Hence, the bacterial strains were incubated with an organic solvent (xylene), and their ability to adhere to the cell surface was tested ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…A commonly used domestic dairy product in Asian countries including Pakistan is “Dahi”; an indigenous yogurt containing a mixture of LAB strains with Lactobacillus bulgaricus and Streptococcus thermophilus as major microbiota. Previous studies have confirmed the presence of LAB, including Lactobacillus bulgaricus (Ali et al., 2019 ), Lactobacillus acidophilus (Farid et al., 2021), and S. thermophilus (Mahmood et al., 2013) in Dahi samples collected from the markets of Rawalpindi and Islamabad, Pakistan.…”
Section: Introductionmentioning
confidence: 76%
“…acidophilus CICC 6074. Furthermore, the surface hydrophobicity of bacteria is strongly linked to their own adhesion properties, indicating that metal ions pre-stress may also enhance the intestinal adhesive colonization of L. acidophilus CICC 6074.…”
Section: Resultsmentioning
confidence: 99%
“…30 The change in surface hydrophobicity of bacteria is generally attributed to a change in the ratio of proteins or polysaccharides on its surface, 31 indicating that Mn 2+ pre-stress may have altered the surface composition of L. acidophilus CICC 6074. Furthermore, the surface hydrophobicity of bacteria is strongly linked to their own adhesion properties, 32 indicating that metal ions pre-stress may also enhance the intestinal adhesive colonization of L. acidophilus CICC 6074.…”
Section: Effect Of Metal Ion Pre-stress On the Cell Membrane Integrit...mentioning
confidence: 99%